Abnormal dewetting of Ag layer on three-dimensional ITO branches to form spatial plasmonic nanoparticles for organic solar cells - Dong, Wan Jae; Yu, Hak Ki; Lee, Jong Lam (Scientific Reports, 2020)
Three-dimensional (3D) plasmonic structures have attracted great attention because abnormal wetting behavior of plasmonic nanoparticles (NPs) on 3D nanostructure can enhance the localized surface plasmons (LSPs). However, previous 3D plasmonic nanostructures inherently had weak plasmonic light absorption, low electrical conductivity, and optical transmittance. Here, we fabricated a novel 3D plasmonic nanostructure composed of Ag NPs as the metal for strong LSPs and 3D nano-branched indium tin oxide (ITO BRs) as a transparent and conductive framework. The Ag NPs formed on the ITO BRs have a more dewetted behavior than those formed on the ITO films. We experimentally investigated the reasons for the dewetting behavior of Ag NPs concerning the geometry of ITO BRs. The spherical Ag NPs are spatially separated and have high density, thereby resulting in strong LSPs. Finite-domain time-difference simulation evidenced that spatially-separated, high-density and spherical Ag NPs formed on ITO BRs dramatically boost the localized electric field in the active layer of organic solar cells (OSCs). Photocurrent of PTB7:PCBM OSCs with the ITO BRs/Ag NPs increased by 14%.